Improvement Strategy of Competitive Advantage and Marketing Performance of Public Market - Endah Budiarti (STKIP Singkawang, 2018)
The purpose of this research is to analyze and prove the influence of customer relationship management (CRM), service quality and entrepreneurship orientation to competitive advantage and marketing performance and to analyze and prove the influence of competitive advantage to marketing performance of the public market in East Java Province. The object of this research is the whole market unit of the public in East Java Province spread over 29 regencies and 9 cities in East Java Province amounting to 335 units of the public market. The unit of analysis (analysis unit) in this research is a revitalized public market that is 67 public market in East Java Province. While the observation unit is a trader or tenant of a community market stand in East Java Province. The number of public market traders in the market that has been revitalized today is 25,000. In this study, researchers measured the marketing performance of the Public market in East Java Province based on the perception of the trader or tenant stand, so the measure of marketing performance is perceptual. The sample used is 190 merchants. The number is spread across 67 units of the public market in East Java Province. The model to be used in this research is the model of causality or relationship. To test the proposed hypothesis, the analysis technique uses SEM (Structural Equation Modeling), with AMOS statistic software. The results of hypothesis testing: Customer relationship management, Quality of service and entrepreneurial orientation significantly influence the competitive advantage of the market public in East Java Province. Customer relationship management and service quality significantly influence the marketing performance of the public market in East Java Province, while the orientation of entrepreneurship has no significant effect on marketing performance of the public market in East Java Province. Competitive advantage influences the marketing performance of public market significantly in East Java Province.